Blue-eyed devil [compact disc, unabridged] - Kleypas, Lisa (Brilliance Audio, 2008)
Returning to town two years after marrying a man of whom her family disapproves, a rebellious heiress is determined to never again fall for the wrong man, until she meets a sexy Texan from the wrong side of the tracks and who is an enemy of her family.